Camouflaging in autism: A systematic review. (November 2021) - Cook, Julia; Hull, Laura; Crane, Laura; Mandy, William
Abstract: Some autistic people employ strategies and behaviours to cope with the everyday social world, thereby 'camouflaging' their autistic differences and difficulties. This review aimed to systematically appraise and synthesise the current evidence base pertaining to autistic camouflaging. Following a systematic search of eight databases, 29 studies quantifying camouflaging in children and adults with autism diagnoses or high levels of autistic traits were reviewed. The multiple methods used to measure camouflaging broadly fell under two different approaches: internal-external discrepancy or self-report. These approaches appear to relate to two distinct but potentially connected elements of camouflaging: observable behavioural presentations and self-perceived camouflaging efforts. While significant variation was noted across individual study findings, much of the existing literature supported three preliminary findings about the nature of autistic camouflaging: (1) adults with more self-reported autistic traits report greater engagement in camouflaging; (2) sex and gender differences exist in camouflaging; and (3) higher self-reported camouflaging is associated with worse mental health outcomes. However, the research base was limited regarding participant characterisation and representativeness, which suggests that conclusions cannot be applied to the autistic community as a whole. We propose priorities for future research in refining the current understanding of camouflaging and improving measurement methods. Highlights: Current approaches to measuring camouflaging appear to measure 'camouflaging intent' and 'camouflaging efficacy'. Adults with more self-reported autistic traits report greater engagement in camouflaging. Sex and gender differences exist in camouflaging. Higher self-reported camouflaging is associated with worse mental health outcomes. Study designs are limited by poor participant characterisation and representativeness.